2016
DOI: 10.1186/s40494-016-0094-1
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of coloured lead glass glitter from an early eighteenth century material collection, Cambridge, by electron microscopy/energy dispersive X-ray analysis

Abstract: Background: Coloured glass glitter is made from thin glass flakes and used for decoration purposes. Published analytical data mainly originates from restoration sites in different countries and is still fragmentary. Samples are often contaminated or corroded, which makes it difficult to evaluate the results, particularly when these were obtained by near-surface techniques.Context and purpose of the study: For this investigation, six types of coloured glass glitter from an eighteenth century material collection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…, Verità ). The green tint induced by Fe 2 O 3 was certainly eliminated by adding MnO and As 2 O 3 (Steigenberger and Herm ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…, Verità ). The green tint induced by Fe 2 O 3 was certainly eliminated by adding MnO and As 2 O 3 (Steigenberger and Herm ).…”
Section: Discussionmentioning
confidence: 99%
“…Copper oxide (generally 2 to >10 wt.% CuO) was commonly used to give the blue colour to turquoise glass in the Middle Ages (Biron et al 1996, Cannella 2006, and tin dioxide was added as opacifier agent (Henderson 2000, Mirti 2002, Tite et al 2008, Greiff 2008, Arletti et al 2011, Thornton et al 2014, Verità 2014. The green tint induced by Fe 2 O 3 was certainly eliminated by adding MnO and As 2 O 3 (Steigenberger and Herm 2016).…”
Section: Relationship Between Chemical Composition and Glass Colourmentioning
confidence: 99%
“…conclude that the painters used local cullet as an additive to oil paint. In contrast to the smalt used by Villalpando in the two paintings in this study, the lead-rich glass found reported byLutzenberger et al (2010) had a very high calcium content.18 The "fritta di cristallo" was obtained calcinating a stone rich in quartz, which Neri describes as "Tarso," with ashes from Levante ("polverino").While Neri describes with detail the making of lead glass, he also references the blue smalt that painters used as an independent material; thus, it is hard to affirm whether or not lead glass was used to paint.19 British lead glass (flint glass) has high contents of lead (between 12 and 40 wt.% PbO)(Steigenberger and Herm 2016;Kurkjian and Prindle 1988;Hellemans et al 2014) in comparison with the content found in Villalpando's paintings.…”
mentioning
confidence: 99%